2001
DOI: 10.1088/1009-9271/1/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Bursts: Afterglows and Central Engines

Abstract: Gamma-ray bursts (GRBs) are most intense transient gamma-ray events in the sky when they are on together with the strong evidences (i.e. the isotropic and inhomogeneous distribution of GRBs detected by BASTE) that they are located at cosmological distances, which make them the most energetic events ever known. For example, the observed radiation energies of some GRBs are equivalent to convert more than one solar mass energy into radiation completely. This is thousand times stronger than that of supernova explo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 148 publications
0
28
0
Order By: Relevance
“…This is the main emphasis of this review. There exist already a number of comprehensive reviews on GRB observations 1,2,3 , on theories of GRB 4,5 and on some general or selected topics 6,7,8,9,10,11,12,13,14,15 . Our purpose here is to provide a review which differs from others in several aspects.…”
Section: Introductionmentioning
confidence: 99%
“…This is the main emphasis of this review. There exist already a number of comprehensive reviews on GRB observations 1,2,3 , on theories of GRB 4,5 and on some general or selected topics 6,7,8,9,10,11,12,13,14,15 . Our purpose here is to provide a review which differs from others in several aspects.…”
Section: Introductionmentioning
confidence: 99%
“…There is little doubt that gamma-ray bursts (GRBs) arise from relativistically expanding winds/fireballs, which also drive relativistic blast waves that are responsible for latertime emission at X-ray, optical, and radio bands (see reviews by Piran 1999;van Paradijs, Kouveliotou, & Wijers 2000;Cheng & Lu 2001;. The observed GRB spectra are hard, with a significant fraction of the energy above the e AE pair formation energy threshold, so it is believable that there are processes of substantial pair production related to GRBs.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplying by m 2 gives p α p α = m 2 , with no restriction on m = m(s). In other words, the energy E 2 = m 2 c 4 u 0 u 0 and the three-momentum p 2 = m 2 c 2 3 i=1 u i u i can still satisfy an equation of the form 2 , even if the mass varies in space-time. In order that these equations describe real particles (with non-negative masses) it is necessary that the five-dimensional metric should have a signature corresponding to ε = −1, thus making the fifth dimension spacelike, in agreement with the conclusion obtained from the study of the time delay of the high energy photon in GRB 940217, and the observed sign of the cosmological constant.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…The fluence of the delayed emission was 7 × 10 −6 in the energy range 30 MeV-3 GeV [1]. For comparison, typical GRBs emit photons in the energy range between a few keV and a few tens of MeV, and last a few tens of seconds [2].…”
Section: Introductionmentioning
confidence: 99%